O dever de casa e a atualidade de sua importância na relação professor-estudante-família: um olhar sobre o primeiro ciclo do ensino fundamental em uma Escola Municipal do bairro da Terra-firme - SANTOS, Luiz Carlos Martins dos (2020)
This article discusses the importance of applying homework in elementary school and more specifically in its first cycle. To this end, it briefly presents the perspective of some authors who have already discussed the subject and advances to field research. Homework is generally a topic barely discussed in Brazil and the fact that there is some consensus as to its application does not mean that there are not several tensions involved in this dialogue; especially when, based on a sociological approach, we analyze the impacts that this activity causes in the relationship between family and school and vice versa; hence the objective of focusing on the interactions that involve this practice. The research was triggered by questions such as: what are the limits and advantages of using homework? What is the opinion of teachers, students and family members regarding their importance? Is it still important to apply this? The methodology used was that of exploratory research, with a qualitative and quantitative approach, involving a bibliographical survey, application of questionnaires, as well as a case study with informal observations and interviews with the social actors involved. The research found that the way to improve education is not the abolition of homework and this is an important tool to extend learning and the main link between family and school. It is therefore valid to invest in this relationship, which must be configured as a two-way street, articulating the school contents to the living space of the students in order to conceive a student not only consumer but also producer of knowledge. Finally, it is a fact that research needs to continue advancing in the study of this subject.